THE DISPLAY OF NATIONAL PECULIARITIES IN ENGLISH AND KARAKALPAK PROVERBS AND SAYINGS: THE DISPLAY OF NATIONAL PECULIARITIES IN ENGLISH AND KARAKALPAK PROVERBS AND SAYINGS - Bekbergenova, Gulaim (Журнал иностранных языков и лингвистики, 2025)
Proverbs and sayings are the product of folk’s art. Each nation or ethnic group has its own proverbs and sayings which reflect customs and traditions, way of life and mentality of people. Proverbs and sayings convey people’s wisdom from generation to generation. As we know, proverbs teach people to do or not to do something. The cultural connotations of phraseological units are defined by cultural values of a certain nation that are specific for it. Cultural connotation emerges as a result of interpretation of associative and image basis of phraseological units in its relation to national-cultural stereotypes, i.e. interpretation of denotative, connotative, and image components.